EPR in the 21st century : basics and applications to material, life, and earth sciences : proceedings of the Third Asia Pacific EPR/ESR Symposium, Kobe, Japan, October 29-November 1, 2001 /: basics and applications to material, life, and earth sciences : proceedings of the Third Asia Pacific EPR/ESR Symposium, Kobe, Japan, October 29-November 1, 2001. (2002) - Unknown
No abstract available